Хрестоматийные тексты русская педагогическая практика XIX в. и поэтический канон - Vdovin, Alexey; Leibov, Roman (Acta Slavica Estonica, 2013)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. The first part of the book contains chapters about the general history of school textbooks for reading and the story of the heritage of two authors (Vyazemsky and Fet) in them. The second part of the book presents chapters on various Russian poets (Batyushkov, Zhukovsky, Pushkin, Koltsov, Tyutchev, Maikov) whose poems found a firm place in the reading materials for schools. The chapters of the monograph give an idea of different aspects of the history of these texts and their reception. The monograph has two supplements. In the first there is a list of 108 textbooks and books of reading which are all included in the unique data base accessible in the Internet (www.ruthenia.ru/canon). The second supplement offers a list of the most popular authors and their texts included in the textbooks of the 19th century.